Auto-fluorescence of the bone and its use for delineation of bone necrosis - Ristow, Oliver; Pautke, Christoph (International journal of oral and maxillofacial surgery, 2014)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a challenging complication of long-term bisphosphonate treatment. Currently, the drawback in the surgical management of BRONJ is the difﬁculty distinguishing between viable and necrotic bone. Intraoperative bone ﬂuorescence induced by tetracyclines has been shown to be a valuable aid to overcome this problem. In this technical note we report the ﬁnding that viable bone is auto-ﬂuorescent using the VELscope Vx ﬂuorescence lamp. Necrotic bone shows an altered ﬂuorescence pattern (pale or no ﬂuorescence). Thus it is suggested that auto-ﬂuorescence of bone might be of similar use during the surgical therapy of BRONJ.